Molecular Insight into Energy Loss in Organic Solar Cells (Communications in Computational Chemistry, 2025)
With the rapid development of A-D-A non-fullerene acceptors, organic solar cells (OSCs) have made significantprogress. However, compared to inorganic and perovskite solar cells, the energy loss in OSCs remains relatively large. In thisPerspective, we summarize our recent computational advances in elucidating the mechanisms of energy loss in OSCs at themolecular level. We highlight strategies to minimize voltage loss during charge generation, suppress triplet-channel recombination,and reduce non-radiative voltage loss by modulating both molecular and aggregation structures.